2021
DOI: 10.1177/03000605211055829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early enteral nutrition on critical care outcomes in patients with acute ischemic stroke

Abstract: Objective Stroke-associated pneumonia (SAP) is a comorbidity of ischemic stroke related to clinical outcomes. Early enteral nutrition (EEN; within 48 hours) reduces the incidence of infection and length of intensive care unit (ICU)/hospital stay. The relationship between EEN and critical care outcomes, including SAP, in patients with ischemic stroke has been insufficiently studied. Methods We recruited 499 patients in this retrospective observational study. We evaluated SAP incidence within 14 days from admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The timing of placement of enteral feeding tubes after the occurrence of stroke has received attention as a potentially important determinant in outcomes. [19][20][21] Despite limited data on this subject and lack of consensus, shorter times between stroke and tube may favor better critical-care outcomes, including stroke-associated pneumonia. 21 In this study, all patients were given enteral nutrition within 48 hours, which accords with current guidelines and expert consensus recommendations, so the timing of gastric tube insertion was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of placement of enteral feeding tubes after the occurrence of stroke has received attention as a potentially important determinant in outcomes. [19][20][21] Despite limited data on this subject and lack of consensus, shorter times between stroke and tube may favor better critical-care outcomes, including stroke-associated pneumonia. 21 In this study, all patients were given enteral nutrition within 48 hours, which accords with current guidelines and expert consensus recommendations, so the timing of gastric tube insertion was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the cause of this correlation has been attributed by some studies to poor sun exposure, by others from a dysfunction of the melanocortin 1 receptor gene [ 116 ], and from others to polymorphism in genes that influence vitamin D levels, especially in children [ 117 ]. Especially in women, it was observed that reduced levels of vitamin D were present in those with MS [ 118 ]. Other data suggest that good vitamin D levels in mother and child may protect against MS [ 119 ].…”
Section: Multiple Sclerosis Vitamin D and Gendermentioning
confidence: 99%
“…To account for extensive dysbiosis of the gut microbiome, probiotic supplementation has been proven to be beneficial in improving patient outcomes through the restoration of this biome [40,56]. Incorporation of probiotics into enteral feeding solutions of ischemic stroke patients has shown to reduce malnutrition, diarrhea, intestinal stress, esophageal reflex, bloating, constipation, gastric retention, gastrointestinal bleeding, mechanical ventilation days, and infections [1,[56][57][58].…”
Section: Emerging Nutritional Enhancersmentioning
confidence: 99%